Exercise-Induced Bundle Branch Block - an Infrequent Incidence - Shakya, Sheelendra; Maskey, Arun (Nepalese Medical Journal, 2020)
We describe an elderly woman who underwent a treadmill test preoperatively and was found to have Exercise-induced Left Bundle Branch Block without chest pain. Coronary angiogram was done which revealed a 70% stenosis in the fi rst diagonal branch of Left Anterior Descending Artery and a 40% lesion in proximal Right Coronary Artery. Available literature attributes rate-dependent transient conduction defects to obstructive lesions of coronary arteries, slow arterial blood fl ow, vasospasms as well as pathology in the Bundle of His.